A carbon-based electrocatalyst and catalyst-supported electrode and its preparation and application

By using MOF-74 as a precursor to perform high temperature carbonization under polymer protection, a carbon-based electrocatalyst with high specific surface area and high conductivity was prepared, which solved the problem of increased electroporation of all vanadium flow batteries under high current density. The electrocatalytic activity and cyclic stability have been improved.

CN115719815BActive Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110981013.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-25
Publication Date
2025-02-18
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

When all-vanadium flow batteries operate at high current density, increased electrodeposition leads to degradation of battery performance, and existing electrode materials have shortcomings in improving catalytic activity and stability.

Method used

Using MOF-74 as a precursor, carbonization is carried out at high temperature under the protection of polymer to form a carbon-based electrocatalyst with a high specific surface area and high conductivity, and a catalyst-supported electrode is obtained by pickling treatment. .

Benefits of technology

The conductivity and catalytic activity of the electrocatalyst are improved, the electrochemical polarization is reduced, and the energy efficiency and cycle stability of all vanadium flow batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115719815B_ABST
    Figure CN115719815B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon-based electrocatalyst and a catalyst-supported electrode and its preparation and application, belonging to the field of energy storage technology batteries. The present invention uses MOF-74 (metal ions are Fe, Co, Ni, Mn) as a precursor, and high-temperature carbonization is carried out under the protection of a polymer (polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, polyether F127), which can suppress the collapse of the pore structure of MOF, and due to the unique carbon-clad metal structure formed by the carbonization of MOF-74, the catalytic graphitization of the carbon layer by the metal can improve the conductivity of the catalyst, and then obtain a carbon-based electrocatalyst and a catalyst-supported electrode with a double-layer hollow porous structure with high specific surface area and high conductivity by pickling treatment. The preparation method of the carbon-based electrocatalyst and the catalyst-supported electrode of the present invention is simple and easy to control, and has excellent energy efficiency, electrocatalytic activity and cycle stability, and is expected to achieve large-scale commercial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage, and particularly relates to a double-layer hollow porous catalyst with high specific surface area and high conductivity, and the preparation and application of a catalyst-supported electrode. Background Art

[0002] In recent years, my country's economy and society are in a stage of rapid development, and the consumption of fossil energy is increasing. This calls for us to make full use of renewable energy. However, due to the intermittent and volatile nature of renewable energy, more than 20% of renewable energy cannot be stored, which will also cause serious damage to the stability of the power grid. This urgently requires large-scale energy storage technology. Among the many energy storage technologies, all-vanadium liquid flow batteries are gradually being used in the field of large-scale energy storage technology due to their flexible design, high safety, high energy efficiency and low cost potential. However, the cost of the battery stack and vanadium salts limits the commercial use of all-vanadium liquid flow batteries. An effective way is to enable all-vanadium liquid flow batteries to operate at higher current density while maintaining higher energy density to reduce the cost of the battery stack, but the increase in current density will lead to increased battery polarization, resulting in a decrease in battery performance.

[0003] As one of the key components of all-vanadium liquid flow batteries, electrodes are closely related to the activation polarization, ohmic polarization and concentration polarization of batteries. Currently, commonly used electrodes are graphite felt and carbon felt, mainly because they have good conductivity, stability and low cost. However, when operating at high current density, the lack of sufficient specific surface area and hydrophilicity will lead to large polarization losses. Therefore, it is necessary to modify the electrodes to improve the catalytic activity, hydrophilicity and stability of the electrodes.

[0004] At present, the modification methods of electrodes mainly include surface functionalization, which improves the hydrophilicity of the electrode surface through oxidation, nitridation and other treatments, but the introduction of functional groups will reduce the conductivity of the electrode; surface structure regulation, which increases the specific surface area of ​​the electrode through etching methods such as KOH and NiO, but this will damage the mechanical properties of the electrode; loading metal catalysts, which will greatly increase the cost for precious metals such as Pt and Pd, and reduce the conductivity of the electrode for metal oxides such as WO3 and Mn3O4; loading carbon-based catalysts with large specific surface areas such as carbon nanotubes and mesoporous carbon can reduce activation polarization to a certain extent, but the pore structure is relatively fragile and cannot meet the long-term stable operation of the battery. Therefore, how to prepare highly active and highly stable catalysts has become a problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above problems, the present invention uses MOF-74 (metal ions can be Fe, Co, Ni, Mn, etc.) as a precursor, and performs high-temperature carbonization under the protection of a polymer (polymer can be PVP, SDS, CTAB, F127), which can inhibit the collapse of the pore structure of MOF, and due to the unique carbon-enclosed metal structure formed by the carbonization of MOF-74, the catalytic graphitization of the carbon layer by the metal can improve the conductivity of the catalyst, and then obtains a carbon-based electrocatalyst and a catalyst-supported electrode with a double-layer hollow porous structure having a high specific surface area and high conductivity through acid washing. The preparation method of the electrocatalyst and the catalyst-supported electrode provided by the present invention is simple and easy to control, and has excellent energy efficiency, electrocatalytic activity and cycle stability.

[0006] To achieve the above purpose, the specific technical solution adopted by the present invention is as follows:

[0007] A method for simultaneously preparing a carbon-based electrocatalyst and a catalyst-supported electrode mainly comprises the following steps:

[0008] (1) preparing solution A: adding a metal salt or its hydrate to an organic solvent and stirring uniformly to obtain a solution A having a metal salt concentration of 0.1-0.5 mol / L; preparing solution B: adding a metal organic ligand and a polymer to an organic solvent and stirring uniformly to obtain a solution B having 0.01-0.05 mol / L of the metal organic ligand and 0.1-300 g / L of the polymer; mixing solution A and solution B at a volume ratio of 1:2-2:1 and stirring uniformly; the metal salt is one of nickel salt, iron salt, cobalt salt or manganese salt, and the metal organic ligand is 2,5-dihydroxyterephthalic acid;

[0009] (2) pouring the mixed solution obtained in step (1) into a reaction kettle, adding electrodes, and hydrothermally reacting at 80-120° C. for 6-36 hours. The obtained product is washed with an alcohol solvent and then dried;

[0010] (3) The dried product obtained in step (2) is calcined at 800-1200° C. for 1-3 h under an inert gas atmosphere, and then treated with an acid to obtain a carbon-based electrocatalyst and a catalyst-supported electrode.

[0011] Furthermore, the nickel salt described in step (1) is one or more of nickel sulfate, nickel chloride, and nickel nitrate; the iron salt is one or more of iron sulfate, iron chloride, and iron nitrate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; and the manganese salt is one or more of manganese sulfate, manganese chloride, and manganese nitrate.

[0012] Furthermore, the organic solvent described in step (1) includes N,N-dimethylformamide, methanol, isopropanol, dimethyl sulfoxide, and N-methylpyrrolidone.

[0013] Furthermore, the polymer described in step (1) includes PVP, SDS, CTAB, F127, preferably PVP.

[0014] Furthermore, the alcohol solvent described in step (2) includes methanol, ethanol, propanol and butanol.

[0015] Furthermore, in step (2), the drying condition is 60-80° C. for 3-6 hours.

[0016] Furthermore, the electrode in step (2) is selected from graphite felt, carbon felt, carbon cloth and carbon paper.

[0017] Furthermore, the inert gas described in step (3) includes nitrogen, helium, argon, and neon.

[0018] Furthermore, the acid used in the acid treatment process in step (3) is 2-6 mol / L sulfuric acid or 4-12 mol / L hydrochloric acid, and the treatment is carried out for 24-48 hours.

[0019] Another aspect of the present invention provides a carbon-based electrocatalyst prepared by the above method and a catalyst-supported electrode.

[0020] Furthermore, the catalyst loading of the electrode is 1-3 mg / cm 2 .

[0021] Another aspect of the present invention provides the use of the above-mentioned carbon-based electrocatalyst and catalyst-supported electrode in an all-vanadium liquid flow battery.

[0022] Furthermore, the catalyst-loaded electrodes are used as positive and negative electrodes of an all-vanadium liquid flow battery.

[0023] Furthermore, the high current density of the vanadium redox flow battery is 80-280 mA / cm 2 .

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) The specific surface area of ​​the carbon-based electrocatalyst prepared by the present invention is 200-500m 2 / g, the pore size distribution of the carbon layer is about 1.5-3.5nm, and the diameter of the hollow part inside the catalyst is about 30-50nm.

[0026] (2) During the hydrothermal reaction in the preparation process of the carbon-based electrocatalyst of the present invention, polyvinyl pyrrolidone (PVP) will interact with nickel ions and be loaded on the surface of MOF particles, which can significantly alleviate particle aggregation and obtain MOF particles with good dispersion and large specific surface area.

[0027] (3) During the high-temperature carbonization process of the carbon-based electrocatalyst preparation process of the present invention, the interface interaction between polyvinyl pyrrolidone (PVP) and MOF can inhibit the collapse of the pore structure of MOF and alleviate the aggregation of metal particles to form carbon-coated nickel particles with a porous structure. In addition, the metal nickel can catalyze the graphitization of the carbon layer during the carbonization process, thereby improving the conductivity of the catalyst. After acid washing, a carbon-based electrocatalyst with a double-layer hollow porous structure having a high specific surface area and high conductivity can be obtained. Since the carbon layer is porous, the vanadium active substance can enter the interior of the catalyst to react, thereby providing sufficient reactive sites for the redox reaction of the vanadium active substance, reducing electrochemical polarization, and improving energy efficiency.

[0028] (4) The carbon-based electrocatalyst of the present invention not only has a high specific surface area, but also has a very stable pore structure, which is conducive to exposing more active sites and can also ensure the stability of the catalyst to meet practical applications.

[0029] (5) The present invention uses in-situ catalyst loading to ensure uniformity of the catalyst loading on the electrode surface, regulates the catalyst loading amount by changing the hydrothermal reaction time, and regulates the conductivity and specific surface area of ​​the catalyst by controlling the carbonization temperature.

[0030] (6) The preparation method of the present invention is simple, the production equipment is conventional, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0032] Figure 1 The SEM and TEM images of the catalyst and the catalyst-supported electrode obtained in Example 2;

[0033] Figure 2 The SEM and TEM images of the catalyst and the catalyst-supported electrode obtained in Example 1;

[0034] Figure 3 This is a SEM photo of a sheet catalyst prepared using Bi-MOF as a precursor in Comparative Example 3;

[0035] Figure 4 This is a SEM photo of a cubic catalyst prepared using ZIF-8 as a precursor in Comparative Example 4;

[0036] Figure 5 This is a comparison of the pore size distribution of the catalyst after acid washing (NMPC-A) and before acid washing (NMPC) in Example 1;

[0037] Figure 6The graphite felt electrode loaded with the catalyst of Example 2 was 2 Cycle performance;

[0038] Figure 7 The structure comparison between the catalyst with a hollow porous structure obtained in Example 1 and the catalyst with a less micropore and mesoporous structure obtained in Example 2 is shown. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0040] Example 1

[0041] A method for simultaneously preparing a carbon-based electrocatalyst and a catalyst-supported electrode mainly comprises the following steps:

[0042] 1) Prepare solution A: add 7.29mmol nickel chloride hexahydrate (NiCl2·6H2O) to 30ml DMF and stir; prepare solution B: add 0.9mmol 2,5-dihydroxyterephthalic acid and 3g PVP to 30ml DMF and stir. Pour solution A into solution B and stir for 2h;

[0043] 2) Pour the mixed solution of A and B into a reactor, add a graphite felt electrode and perform hydrothermal reaction at 100°C for 24 hours. Rinse the product after hydrothermal reaction with ethanol for more than three times and then dry it;

[0044] 3) The dried product was calcined at 1000° C. for 2 h in a nitrogen atmosphere with a heating rate of 5° C. / min, and then treated with 3 mol / L sulfuric acid to obtain a carbon-based electrocatalyst and a catalyst-supported graphite felt electrode.

[0045] The SEM and TEM images of the prepared carbon-based electrocatalysts are shown in Figure 2 As shown, it can be seen that the catalyst is a hollow carbon sphere of about 40 nm coated with PVP sintered carbon.

[0046] Figure 2 It shows that the catalyst-loaded electrode obtained by adding PVP in Example 1 ( Figure 2 a) and a catalyst ( Figure 2 bd) can be evenly dispersed without obvious aggregation, and the metal nickel can be completely removed after pickling ( Figure 2 c), a spherical hollow structure was obtained, and Figure 2In (d), the content of vanadium active substances was analyzed in the carbon layer and the central area by EDS, and it was found that the vanadium content in the central area was much higher than that in the carbon layer area, indicating that the vanadium active substances can react in the internal space of the spherical shell.

[0047] The catalyst loading of the catalyst-loaded graphite felt electrode of the present invention is 1-3 mg / cm 2 The preparation method is simple and easy to operate, the electrode structure is controllable, and it has excellent electrochemical activity and cycle stability. The assembled all-vanadium liquid flow battery consists of three parts: positive and negative electrolyte storage tanks, pumps and single cells. The positive and negative electrolytes are both 0.8MV 3+ +0.8MV 4+ +3M H2SO4, the amount of electrolyte is 3.5ml / cm 2 The obtained graphite felt electrode with catalyst loading was used as positive and negative electrodes, the electrode thickness was 2 mm, and the surface area of ​​the two sides of the electrode was 3*4 cm 2 ; Nafion212 membrane is the middle diaphragm, at 80-280mA / cm 2 The battery is charged and discharged at a constant current density of , and the charge and discharge cut-off voltage is 1.55V, and the discharge cut-off voltage is 1.0V.

[0048] The prepared catalyst-supported graphite felt electrode was 2 The cycle performance of Figure 5 As shown, the prepared electrode is 2 The energy efficiency reaches 82.5% under these conditions.

[0049] Example 2

[0050] The preparation method and process are the same as those in Example 1, except that PVP is not added;

[0051] Figure 1 It shows that the catalyst-loaded electrode ( Figure 1 a) and a catalyst ( Figure 1 bd) showed obvious aggregation. The catalysts obtained after acid washing ( Figure 1 c) A large amount of metallic nickel was not removed, a hollow structure could not be obtained, and the catalyst structure was severely distorted ( Figure 1 d), compared with the spherical hollow structure, the catalytic active sites are insufficient.

[0052] Example 3

[0053] The preparation method and process are the same as those in Example 1, except that the hydrothermal reaction time is 6 h and the carbonization temperature is 800°C;

[0054] Example 4

[0055] The preparation method and process are the same as those in Example 1, except that the hydrothermal reaction time is 12 h and the carbonization temperature is 800°C;

[0056] Example 5

[0057] The preparation method and process are the same as those in Example 1, except that the hydrothermal reaction time is 36 h and the carbonization temperature is 800° C.;

[0058] Example 6

[0059] The preparation method and process are the same as those in Example 1, except that the carbonization temperature is 800°C;

[0060] Example 7

[0061] The preparation method and process are the same as those in Example 1, except that the carbonization temperature is 1200°C;

[0062] Comparative Example 1

[0063] 1) Wash and dry the flake graphite felt electrode;

[0064] The specific operation of cleaning is: rinse the 3*4cm sheet of graphite felt (electrode thickness is 2mm) with deionized water three times and then with anhydrous ethanol three times, and then ultrasonically clean it in an ethanol-water solution with a volume ratio of 1:1 for 40 minutes;

[0065] 2) Drying treatment The specific operation is: placing the cleaned graphite felt in a vacuum drying oven at 80°C for 4 hours to obtain a dried graphite felt electrode;

[0066] 3) Using dried graphite felt electrodes as positive and negative electrodes, the assembled all-vanadium liquid flow battery consists of three parts: positive and negative electrolyte storage tanks, pumps and single cells. The positive and negative electrolytes are both 0.8MV 3+ +0.8MV 4+ +3M H2SO4, the amount of electrolyte is 3.5ml / cm 2 The obtained dried graphite felt electrode is used as the positive and negative electrodes, the electrode thickness is 2 mm, and the surface area of ​​the two sides of the electrode is 3*4 cm 2 ; Nafion212 membrane is the middle diaphragm, at 80-280mA / cm 2 The battery is charged and discharged at a constant current density of , and the charge and discharge cut-off voltage is 1.55V, and the discharge cut-off voltage is 1.0V.

[0067] The maximum current density of the prepared graphite felt electrode can only reach 120mA / cm 2 , the energy efficiency is only 67.8%.

[0068] Comparative Example 2

[0069] 1) Wash and dry the sheet-like carbon felt electrode;

[0070] The specific operation of cleaning is: rinse the 3*4cm sheet of carbon felt (electrode thickness is 2mm) with deionized water three times and then with anhydrous ethanol three times, and then ultrasonically clean it in an ethanol-water solution with a volume ratio of 1:1 for 40 minutes;

[0071] 2) Drying treatment The specific operation is: placing the cleaned graphite felt in a vacuum drying oven at 80°C for 4 hours to obtain a dried graphite felt electrode;

[0072] 3) The dried carbon felt electrodes are used as the positive and negative electrodes. The assembled all-vanadium redox flow battery consists of three parts: positive and negative electrolyte storage tanks, pumps and single cells. The positive and negative electrolytes are both 0.8MV 3+ +0.8MV 4+ +3M H2SO4, the amount of electrolyte is 3.5ml / cm 2 The obtained dried carbon felt electrodes are used as positive and negative electrodes, the electrode thickness is 2 mm, and the surface area of ​​the two sides of the electrode is 3*4 cm 2 ; Nafion212 membrane is the middle diaphragm, at 80-280mA / cm 2 The battery is charged and discharged at a constant current density of , and the charge and discharge cut-off voltage is 1.55V, and the discharge cut-off voltage is 1.0V.

[0073] Comparative Example 3

[0074] 1) Prepare solution A: add 0.31mmol bismuth nitrate pentahydrate to 30ml methanol and stir; prepare solution B: add 3.57mmol 1,3,5-benzenetricarboxylic acid to 30ml methanol and stir. Pour solution A into solution B and stir for 2h;

[0075] 2) Pour the mixed solution of A and B into a reactor, add a graphite felt electrode and perform hydrothermal reaction at 120°C for 24 hours. Rinse the product after hydrothermal reaction with methanol for more than three times and then dry it;

[0076] 3) The dried sample was calcined at 1000°C for 3 h in a nitrogen atmosphere with a heating rate of 5°C / min to obtain a catalyst-loaded graphite felt electrode.

[0077] Figure 3 It shows that the solid catalyst-supported electrode obtained by Bi-MOF can only react on the electrode surface. Compared with the porous hollow spherical structure in Example 1 (the internal space can be used), the catalytic active sites are insufficient.

[0078] The obtained catalyst-loaded graphite felt electrode is used as the electrode of the all-vanadium liquid flow battery. The assembled all-vanadium liquid flow battery consists of three parts: positive and negative electrolyte storage tanks, pumps and single cells. The positive and negative electrolytes are both 0.8MV 3+ +0.8MV 4+ +3MH2SO4, the amount of electrolyte is 3.5ml / cm 2 The obtained graphite felt electrode with catalyst loading was used as positive and negative electrodes, the electrode thickness was 2 mm, and the surface area of ​​the two sides of the electrode was 3*4 cm 2 ; Nafion212 membrane is the middle diaphragm, at 80-280mA / cm 2 The battery is charged and discharged at a constant current density of , and the charge and discharge cut-off voltage is 1.55V, and the discharge cut-off voltage is 1.0V.

[0079] Comparative Example 4

[0080] 1) Prepare solution A: add 11.77 mmol zinc nitrate pentahydrate into 150 ml methanol and stir; prepare solution B: add 85.37 mmol 2-methylimidazole into 150 ml methanol and stir; pour solution A into solution B and stir for 2 h;

[0081] 2) Pour the mixed solution of A and B into a reactor, add a graphite felt electrode and react at room temperature for 24 hours. The hydrothermal product is washed with methanol for more than three times and then dried;

[0082] 3) The dried sample was calcined at 1100° C. for 1 h in a nitrogen atmosphere with a heating rate of 5° C. / min to obtain a catalyst-supported graphite felt electrode.

[0083] Figure 4 It shows that the electrode supported by the sheet catalyst obtained from ZIF8 can only react on the electrode surface. Compared with the porous hollow spherical structure in Example 1 (the internal space can be used), the catalytic active sites are insufficient.

[0084] The obtained catalyst-loaded graphite felt electrode is used as the electrode of the all-vanadium liquid flow battery. The assembled all-vanadium liquid flow battery consists of three parts: positive and negative electrolyte storage tanks, pumps and single cells. The positive and negative electrolytes are both 0.8MV 3+ +0.8MV 4+ +3MH2SO4, the amount of electrolyte is 3.5ml / cm 2 The graphite felt electrodes loaded with catalysts obtained in the single cell are used as positive and negative electrodes. The electrode thickness is 2 mm, and the surface area of ​​the two sides of the electrode is 3*4 cm 2 ; Nafion212 membrane is the middle diaphragm, at 80-280mA / cm 2The battery is charged and discharged at a constant current density of , and the charge and discharge cut-off voltage is 1.55V, and the discharge cut-off voltage is 1.0V.

[0085] Table 1. Current density at 200 mA cm -2 Battery performance comparison

[0086]

[0087] In Example 1, the catalyst protected by PVP during high-temperature sintering can maintain the integrity of the pore structure, the particles are evenly distributed, there is no obvious aggregation, and the metal nickel can be removed to obtain a carbon-based electrocatalyst with a double-layer hollow porous structure with high specific surface area and high conductivity, which has high electrocatalytic activity and stability. However, in Example 2, the catalyst without PVP protection has a distorted and collapsed structure, and due to the collapse of the pore structure, some metal nickel particles cannot be removed, which will cause serious hydrogen evolution. Compared with Example 1, the electrochemical performance is significantly reduced. In Examples 3, 4, and 5, the effect of the catalyst loading on the battery performance is explored by controlling the hydrothermal reaction time. It is finally determined that the hydrothermal reaction time is 24h and the catalyst loading is 1-2mg cm -2 It has high electrochemical performance; Examples 6 and 7 explored the effect of carbonization temperature on electrode performance. At 800°C, the catalyst could not stably adhere to GF, resulting in decreased cycle stability of the battery. At 1200°C, the high temperature caused the collapse of the catalyst structure and the loss of oxygen-containing functional groups, which damaged the battery performance. Finally, the optimal carbonization temperature was determined to be 1000°C; In Comparative Example 1, the graphite felt electrode without catalyst loading had low electrochemical activity and poor performance; In Comparative Example 2, the carbon felt had poor operating performance at higher current density and could not meet the actual commercialization requirements. Application; Comparative Examples 3 and 4, the flaky and cubic catalysts obtained from Bi-MOF and ZIF-8 as precursors cannot provide sufficient reaction sites for vanadium active substances due to the collapse of the pore structure and the adhesion between particles during the carbonization process. Moreover, the carbon material has obviously insufficient conductivity and poor performance due to the lack of metal catalytic graphitization. Therefore, it is determined that the double-layer hollow porous structure carbon-based electrocatalyst with high specific surface area and high conductivity obtained from Ni-MOF under the auxiliary protection of PVP is very suitable as an electrocatalyst for all-vanadium liquid flow batteries.

[0088] Figure 5a shows a comparison of the pore structures of the catalyst (NMPC) obtained in Example 1 and the catalyst (NMC) obtained in Example 2. It is found that the catalyst (NMPC) obtained in Example 1 has more micropores and mesopores, which can better allow the acid to enter the interior of the spherical shell to etch and remove nickel, thereby obtaining a porous hollow structure. However, the catalyst (NMC) obtained in Example 2 has fewer micropores and mesopores, which cannot allow the acid to enter, and the metal nickel cannot be removed, and its internal space cannot be utilized, so the active sites are also insufficient. Figure 5 b also confirmed that after acid washing, the mesoporous structure of NMPC in Example 1 increased and the specific surface area increased from 96m 2 / g increased to 295m 2 / g, the active sites increased by 2 times.

[0089] Figure 6 It shows that the catalyst-supported electrode obtained in Example 1 has a high conductivity at 200 mA / cm 2 The long cycle performance of the prepared catalyst-loaded electrode is almost unchanged in the long cycle of 1000 cycles.

[0090] Figure 7 It shows that the catalyst with a hollow porous structure obtained in Example 1 has a structural advantage over the catalyst with fewer micropores and mesoporous structures obtained in Example 2, and the catalyst obtained in Example 2 can only allow the active substance to participate in the reaction on the surface. At the same time, compared with the sheet catalyst prepared by Bi-MOF and the solid catalyst prepared by ZIF8 in Comparative Examples 3 and 4, these two catalysts can only allow the vanadium active substance to react on the electrode surface, and the active sites are insufficient, while the catalyst obtained in Example 1 can allow the vanadium active substance to participate in the reaction on the surface and inside of the spherical shell, and has more catalytic active sites.

[0091] Table 2. Comparison of catalyst loading in electrodes obtained from Example 1 (NMPC-A-GF), Example 2 (NMC-A-GF) and Comparative Example 1 (GF)

[0092]

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for simultaneously preparing a carbon-based electrocatalyst and a catalyst-supported electrode, characterized in that: The steps include: (1) preparing solution A: adding a metal salt or its hydrate to an organic solvent and stirring uniformly to obtain a solution A having a metal salt concentration of 0.1-0.5 mol / L; preparing solution B: adding a metal organic ligand and a polymer to an organic solvent and stirring uniformly to obtain a solution B having 0.01-0.05 mol / L of the metal organic ligand and 0.1-300 g / L of the polymer; mixing solution A and solution B at a volume ratio of 1:2-2:1 and stirring uniformly; the metal salt is one of nickel salt, iron salt, cobalt salt or manganese salt, and the metal organic ligand is 2,5-dihydroxyterephthalic acid; (2) pouring the mixed solution obtained in step (1) into a reaction kettle, adding electrodes, and hydrothermally reacting at 80-120° C. for 6-36 hours. The obtained product is rinsed with an alcohol solvent and then dried; (3) calcining the dried product obtained in step (2) at 800-1200° C. for 1-3 h under an inert gas atmosphere, and then treating with an acid to obtain a carbon-based electrocatalyst and a catalyst-supported electrode; The polymer described in step (1) includes PVP, SDS, CTAB, and F127; The electrode in step (2) is selected from graphite felt, carbon felt, carbon cloth and carbon paper.

2. The method according to claim 1, characterized in that The nickel salt described in step (1) is one or more of nickel sulfate, nickel chloride, and nickel nitrate; the iron salt is one or more of iron sulfate, iron chloride, and iron nitrate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; and the manganese salt is one or more of manganese sulfate, manganese chloride, and manganese nitrate.

3. The method according to claim 1, characterized in that The organic solvent described in step (1) includes N,N-dimethylformamide, methanol, isopropanol, dimethyl sulfoxide, and N-methylpyrrolidone.

4. The method according to claim 1, characterized in that: The alcohol solvent described in step (2) includes methanol, ethanol, propanol and butanol.

5. The method according to claim 1, characterized in that The drying condition in step (2) is 60-80° C. for 3-6 hours.

6. The method according to claim 1, characterized in that The inert gas described in step (3) includes nitrogen, helium, argon and neon.

7. The method according to claim 1, characterized in that The acid used in the acid treatment process in step (3) is 2-6 mol / L sulfuric acid or 4-12 mol / L hydrochloric acid, and the treatment is carried out for 24-48 hours.

8. The carbon-based electrocatalyst and catalyst-supported electrode prepared by the method according to any one of claims 1 to 7.

9. The carbon-based electrocatalyst and catalyst-supported electrode according to claim 8, characterized in that: The catalyst loading of the electrode is 1-3 mg / cm 2 .

10. Use of the carbon-based electrocatalyst and catalyst-supported electrode according to claim 8 or 9 in an all-vanadium liquid flow battery.

Citation Information

Patent Citations

  • Preparation method and application of M-MOF-74 / graphene composite cathode material

    CN109638304A

  • Porous electrode for flow battery and preparation method of porous electrode

    CN111785978A